Genomic characteristics of ST6115 carbapenem-resistant Klebsiella pneumoniae coharboring blaNDM-1 and blaIMP-4 - Xie, Xiaofang; Zhai, Yaxuan; Zhu, Zhichen; Qian, Feinan; Zhu, Jie; Gao, Qizhao; Du, Hong (Frontiers in Microbiology, 2025)
ObjectivesThe aim of this study is to characterize the genomic features of ST6115 carbapenem-resistant Klebsiella pneumoniae (CRKP) co-harboring blaNDM-1 and blaIMP-4.MethodsThe genome sequences of one ST6115 Klebsiella pneumoniae (KP) strain and 12 ST17 KP strain were obtained through whole genome sequencing (WGS). Subsequently, a phylogenetic analysis was employed to ascertain the clonal relationship of these strains. The antimicrobial susceptibility testing (AST) was evaluated through the application of the minimum inhibitory concentration (MIC) methodology by the broth microdilution method. Annotation and analysis of the genome enabled the identification of the plasmid structure and the comparative analysis of the genetic background. Finally, the conjugation transfer experiment was conducted to assess the transferability of the plasmid pHD8428-NDM-IMP.ResultsA comparable phylogenetic analysis revealed that ST6115 HD8428 and the majority of ST17 strains (9/12) were clustered on the same clade, which suggests a close relationship between two ST types. Additionally, HD8428 showed particularly close genetic similarity to HD11490, with a single-nucleotide polymorphism (SNP) difference of only 273. The analysis of the antibiotic resistance genes carried by the 13 strains revealed that all strains carry extended-spectrum β-lactamase (ESBL) genes. AST revealed that HD8428 exhibited resistance to a diverse range of antibiotics. The blaNDM-1 and blaIMP-4 genes were identified as being located on the plasmid pHD8428-NDM-IMP. Further analysis demonstrated that the blaNDM-1 gene was present on ΔTn125, while the blaIMP-4 gene was located on In1377-2. The results of the conjugation experiment indicated that plasmid pHD8428-NDM-IMP may pose a risk for the transmission of antibiotic resistance in healthcare settings.ConclusionWe report a clinical ST6115 strain HD8428 and identify the coexistence of blaNDM-1 and blaIMP-4 in the IncHI5 type plasmid pHD8428-NDM-IMP. HD8428 was resistant to a wide range of antibiotics and harbored the transmissible plasmid pHD8428-NDM-IMP, which made it a potential threat to public health. Our study indicates that the healthcare system and services should remain vigilant regarding the spread and prevalence of ST6115.